Persaingan Maskapai Penerbangan Domestik Dan Perkembangannya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Over the years, the airlines industry in Indonesia and throughout the world has seen rapid growth triggered by spiraling consumer demand for air transportation. Today, all airlines are flying increasing numbers of passengers. The number of-Indonesian air passengers is growing on both domestic and international flights, but as yet Indonesian airlines have been unable to rake the advantage of this demand in growth. This is evident from a domestic seat load factorofjust5Opercent to 60 percent makingfor intense competition among domestic airlines. Domestic airlines currently providing scheduled services are Garuda Indonesia, Merpati Nusantara, Sempati Air, Mandala Airlines, Bouraq Indonesia Airlines and Dirgantara Air Service. Of the six, Garuda Indonesia dominates international fligh t services, and Merpati Nusantara domestic flight services. To gain from the growing domestic and international demand for air transportation, all domestic airlines need to improve the services they offer. Improvements in air transportation infrastructure are also essential to the growth of the Indonesian air transportation industry.